The Realization of Teachers’ Code Switching in Instructional Process. - Musmuliadi, Musmuliadi; Mujiyanto, Januarius; Sutopo, Djoko (English Education Journal, 2018)
The objectives of this study were to explain the way teachers switch their language in instructional process, to explain the students’ understanding of teachers’ code-switching instructional process in the classroom, and to explain the students’ perception of teachers’ code-switching in instructional process.This research employed qualitative research. The subjects of this study were 3 English teachers and 152 students of SMA Al-Mas’udiyah Bandungan. The data were collected by using audio recording, test, questionnaires, and observation. The results of this study showed that first, there were three ways of english teacher to switch their language in instructional process those are: Inter-sentential code switching, Intra-sentential switching and Emblematic/tag switching. Second, students’ mean score were less than 70. Meaning that, the students understanding of teachers' code switching is categorized low understanding. Third, the students’ perception indicated to positive perception because the majority of students (45%) stated agree with those statements, followed (38%) students stated strongly agree with those statements. Meanwhile, (17%) of the students stated disagree with those statements.